2022
DOI: 10.1177/14713012221096982
|View full text |Cite
|
Sign up to set email alerts
|

Using Twitter to understand perspectives and experiences of dementia and caregiving at the beginning of the COVID-19 pandemic

Abstract: The COVID-19 pandemic has placed a tremendous burden on all of society, particularly among vulnerable populations such as people living with dementia and their caregivers. Efforts to understand the impact of the COVID-19 pandemic on those living with dementia are crucial towards addressing needs during the pandemic and beyond. This qualitative descriptive study includes a thematic analysis of 6938 tweets from March 17–24, 2020, that included direct or indirect references to COVID-19 and at least one of the fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…Similar to existing studies [ 36 , 37 ], our study on Twitter discourse found that many tweets shared experiences of dementia. More specifically, people shared personal narratives related to issues of grief, bereavement, and death of family members with dementia.…”
Section: Discussionsupporting
confidence: 87%
“…Similar to existing studies [ 36 , 37 ], our study on Twitter discourse found that many tweets shared experiences of dementia. More specifically, people shared personal narratives related to issues of grief, bereavement, and death of family members with dementia.…”
Section: Discussionsupporting
confidence: 87%
“…Structural stigma (institutional policies and practices) was strongly connected to the theme of human rights and deprived dignity. More specifically, the right to life and dignity were substantial COVID-19 issues impacting people living with dementia ( 22 , 23 , 34 ). Human rights issues were often related to institutional COVID-19 policies, lockdowns, social isolation, confinement, elder abuse, restraint use, overmedication, overcrowding, understaffing, and ageism, especially within institutional settings ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cipriani and colleagues assert that the coronavirus brought an increase in social isolation, loneliness, and seclusion for people living with dementia ( 23 ). Moreover, inequitable access to ventilators and life-saving services challenged the right to life and raised ethical concerns for people with dementia ( 22 , 23 , 34 ). Family care partners often felt pressured to sign do not resuscitate orders, and people living with dementia were not provided with the same level of care or medical interventions (e.g., ventilators, vaccinations, physician visits, acute care beds, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…Given that existing Twitter studies already explore the early stages of the pandemic (ie, February 15-September 7, 2020, and March 17-24, 2020) on people with dementia [ 19 , 21 ], our study’s time frame focused further into the pandemic (ie, September 8, 2020, to December 8, 2021). Our full set of search terms included “dementia” OR “Alzheimer” used in combination with “COVID-19” OR “COVID” OR “Corona,” resulting in 110,528 tweets.…”
Section: Methodsmentioning
confidence: 99%